Cell wall composition and digestibility alterations in Brachypodium distachyon achieved through reduced expression of the UDP-arabinopyranose mutase - Rancour, David M.; Hatfield, Ronald D.; Marita, Jane M.; Rohr, Nicholas A.; Schmitz, Robert J. (Frontiers in Plant Science, 2015)
Nucleotide-activated sugars are essential substrates for plant cell-wall carbohydrate-polymer biosynthesis. The most prevalent grass cell wall sugars are glucose (Glc), xylose (Xyl), and arabinose (Ara). These sugars are biosynthetically related via the UDP-sugar interconversion pathway. We sought to target and generate UDP-sugar interconversion pathway transgenic Brachypodium distachyon lines resulting in cell wall carbohydrate composition changes with improved digestibility and normal plant stature. Both RNAi-mediated gene-suppression and constitutive gene-expression approaches were performed. Cell walls from 336 T0 transgenic plants with normal appearance were screened for complete carbohydrate composition. RNAi mutants of BdRGP1, a UDP-arabinopyranose mutase, resulted in large alterations in cell wall carbohydrate composition with significant decreases in cell wall Ara content but with minimal change in plant stature. Five independent RNAi-RGP1 T1 plant lines were used for in-depth analysis of plant cell walls. Real-time PCR analysis indicated that gene expression levels for BdRGP1, BdRGP2 and BdRGP3 were reduced in RNAi-RGP1 plants to 15-20% of controls. Cell wall Ara content was reduced by 23-51% of control levels. No alterations in cell wall Xyl and Glc content were observed. Corresponding decreases in cell wall ferulic acid (FA) and ferulic acid-dimers (FA-dimers) were observed. Additionally, cell wall p-coumarates (pCA) were decreased. We demonstrate the cell wall pCA decrease corresponds to Ara-coupled pCA. Xylanase-mediated digestibility of RNAi-RGP1 Brachypodium cell walls resulted in a near two-fold increase of released total carbohydrate. However, cellulolytic hydrolysis of cell wall material was inhibited in leaves of RNAi-RGP1 mutants. Our results indicate that targeted manipulation of UDP-sugar biosynthesis can result in biomass with substantially altered compositions and highlights the complex effect cell wall composition has on digestibility.